2012
DOI: 10.1515/hmbci-2012-0029
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone protects the lower urinary tract from metabolic syndrome-induced alterations

Abstract: Epidemiological studies document a positive and independent association between metabolic syndrome (MetS) and lower urinary tract symptoms (LUTS). In the male, the pathogenesis of MetS-related LUTS involves a complex interplay among pathophysiological mechanisms mainly affecting the prostate and the bladder. Recently, hypogonadism has been recognized as a key factor bridging MetS and LUTS. Preclinical data have evidenced that MetS-induced hypogonadism is associated with alterations not only of the prostate but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A previous in vitro study found that oxidized low‐density lipoprotein can induce and sustain inflammatory response in human prostatic cells through the secretion of interleukin 6 (IL‐6), IL‐8, and basic Fibroblast growth factors (bFGF; Vignozzi et al ., ). Other studies further reported that IL‐8 and bFGF can recruit CXCR1‐ and CXCR2‐positive leukocytes and CD15+ neutrophils and lead to prostate cell hyperplasia (Penna et al ., ; Vignozzi et al ., ,b, ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A previous in vitro study found that oxidized low‐density lipoprotein can induce and sustain inflammatory response in human prostatic cells through the secretion of interleukin 6 (IL‐6), IL‐8, and basic Fibroblast growth factors (bFGF; Vignozzi et al ., ). Other studies further reported that IL‐8 and bFGF can recruit CXCR1‐ and CXCR2‐positive leukocytes and CD15+ neutrophils and lead to prostate cell hyperplasia (Penna et al ., ; Vignozzi et al ., ,b, ).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown a significant association of MetS with BPH (Vignozzi et al ., , ,b; Corona et al ., ; Vignozzi et al ., ; Gacci et al ., , ; Yin et al ., ). In particular, the association between hyperlipidemia and BPE has proven to be very significant and has drawn much attention (Gacci et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, BPH is considered a common etiology of LUTS but this is not an inevitable correlation. The association between LUTS and obesity, metabolic syndrome (MetS), and erectile dysfunction is established at epidemiological level [ 4 5 ]. As potential biological mechanism prostatic inflammation resulting from the immunologic response of pathogenic noxae is discussed to be involved in the development and progression of chronic prostatic diseases such as BPH [ 6 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analysis reveals that the metabolic syndrome was associated with a greater prostate volume increment [16] . In addition, other report suggests that patients with metabolic syndrome presented higher obstructive urinary symptoms score and lower uroflowmetric parameters as compared with those without metabolic syndrome [17] , [18] . In this context, oxidized low-density lipoprotein led to the high secretion of IL-6, IL-8, and bFGF, which are surrogate markers of prostate inflammation on human prostatic myofibroblastic cells [19] .…”
Section: The Relationship Between Bph-associated Prostate Inflammatiomentioning
confidence: 92%